SEED PRIMING ENHANCES CANOLA (BRASSICA NAPUS L.)YIELD BY MODULATING BIOCHEMICAL AND PHYSIOLOGICAL PROPERTIES UNDER WATER DEFICIT CONDITION - K. Khanum; S. A. Majid; A. Bibi; A. Ulfat; S. Ashraf (Journal of Animal and Plant Sciences, 2019)
Canola (Brassica napus L.) is exposed to many environmental pressures that limit its development and yield. Hormonal seed priming is used to cope with adverse effects of stresses. Recent study was conducted to observe  the influence of deficiency of water on growth and other developmental aspects of canola. Experiment was designed for two consective years i.e. 2014-15 and 2015-16  in Randomized complete block design with three replicates. Two rapeseed varieties after priming with different phytohormones viz. Indole acetic acid (IAA),Gibberellic acid (GA), Salicylic acid (SA) and Nitric oxid (NO) were used in 10-4 and 10-5M concentration to study their role in mitigating stress effects. Total soluble sugars, protein and proline accumulation was found to increase under drought stress. Antioxidant enzymes showed varied response, while decrease in relative water contents and cell membrane thermostability was observed due to drought. Hormonal seed soaking was found to somewhat maintain biochemistry and physiology of Canola even under drought stress. Hence it is concluded that hormonal seed soaking is a best strategy to decrease the effects of stress in canola.
Keywords: Canola; Seed priming; Drought; Phytohormones; Catalase; Protein